The impact of economic policy uncertainty on the innovation in China: Empirical evidence from autoregressive distributed lag bounds tests - Hummera Saleem; Jiandong Wen; Muhammad Bilal Khan (Cogent Economics & Finance, 2018)
This study is the first attempt to scrutinize the causal relationship between economic policy uncertainty (EPU) and innovation in the case of China, using the autoregressive distributed lag (ARDL) approach to co-integration approach of innovation accounting for causality analysis. The empirical findings show that EPU can negatively affect innovation. EPU indicates a significantly negative impact on innovation as well as on the gross domestic product (GDP) growth rate. The combined results based on ARDL, innovation accounting approach (IAA) (variance decompositions and impulse response functions), and fully modified ordinary least square (FMOLS) raise an important point that calls for attention. The point is relating to the causality running from EPU to innovation. The future of China is uncertain, so when the economic uncertainty is higher, it lowers the value of future activities of the economy of China.
Keywords: 330; innovation; economic policy uncertainty; causality analysis